Distribution of metals in coastal sediment from northwest Sabah, Malaysia - Ling, Sin Yi; Junaidi Asis; Baba Musta (Elsevier Ltd, 2023)
The type of minerals in sediments control the geochemical distribution of metals which serve as an indicator of the pollution status to the marine environment. The type of minerals was determined from X-ray diffraction (XRD) and scanning electron microscope (SEM) which shows the dominance of carbonate (calcite, aragonite, dolomite), silicate (quartz) and minor clay (illite, kaolinite) minerals. The elemental concentrations were also determined using the Inductively Coupled Plasma (ICP-OES) analysis that shows the major elements Ca > Fe > Mg > Al > Mn for all locations, whereas the heavy metals differ as Ni > Cr > Zn > Co > Pb, Cr > Ni > Zn > Pb > Co and Zn > Pb > Cr > Ni, respectively. The correlation between the major elements and heavy metals were also performed using the Pearson Correlation analysis via IBM SPSS which showed the positive Al–Fe–Mn correlation with the heavy metals but negative correlation with Ca. The correlations between the elements were influenced by the adsorption and precipitation of the major minerals in the sediment. The objective of this study is to determine the geochemical distribution of metals due to the influence of minerals in the coastal sediment of Kota Belud, Kudat and Mantanani Island. Therefore, this study could serve as a geochemical baseline data to understand the abundance of metals from the coastal region of northwest Sabah, Malaysia.